Factors That Influence Public Interest In Choosing Islamic Bank Financing Products - Syahriyatul Muharromah; Huda, Nurul; Muslikh, Muslikh; Rini, Nova (LPPM Universitas Terbuka, 2021)
This study aims to determine the effect of Knowledge, attitudes, subjective norms, behavioral control, and Religiosity on public interest and their impact on Islamic bank financing decisions in DKI Jakarta Province. This study uses the SEM AMOS analysis model with the consumption behavior variables, including Knowledge, attitudes, subjective norms, behavioral control, and Religiosity as exogenous variables. In contrast, the intervening variable is a public interest, and the endogenous variable is the financing decision. The results of this study indicate the variables of knowledge and behavior control have a positive and significant effect on people's interest in using Islamic bank financing products. Attitude and religiosity variables have a positive but not significant impact on people's interest in using Islamic bank financing products. Subjective norms have a negative but insignificant effect on people's attention. Knowledge has a positive and significant impact on people's decisions to choose financing products in Islamic banks. In contrast, Religiosity has a significant adverse effect on the decision to choose financing products in Islamic banks. The variable of public interest has a positive and significant impact on financing decisions. Meanwhile, the indirect effect of the public interest variable cannot significantly mediate the influence of Knowledge and Religiosity on financing decisions.